Development Beyond Neoliberalism? - David Craig , Doug Porter (Routledge, 2006)
This book, like Development, is a tightly packed suitcase of ideas that we wrote over eight years in more than a dozen places. We worked separately and only for short periods together, in touch by email daily and more, and meeting every few months when, over several days, the whole book would go up on a white board or sheets of butcher paper or cafÃ© napkins and notebooks, and all the arguments and cases would be reworked, more often than not from first principles. We wrote the book around these meetings: in Manila, Brisbane, Cairns, Thursday Island, Islamabad and Peshawar, Kampala, Singapore and Hong Kong, Auckland, Mullumbimby, Napier, Raglan, Phnom Penh and numerous points between. However others judge the result, it was for both of us a great and polychrome intellectual adventure, as well as a more personal attempt to make critical sense of our different working experiences.